Bifocal herpes simplex in a child. - Milano, A. (European Journal of Pediatric Dermatology, 2018)
HS in the child hardly ever begins with a clinically evident primary infection such as neonatal herpes, herpetic gingivostomatitis, herpetic eruption on previous dermatitis or HS zosteriform. The first clinically evident cutaneous manifestation is usually recurrent HS which in most cases is localized to the cheek. Localization in the hand is not common in the child and may occur as a primary, sometimes zosteriform HS, and post-primary infection. The post-primary HS of the hand may follow a primary infection, usually zosteriform HS, of the same hand, it may accompany a primary herpetic gingivostomatitis due to autoinoculation for sucking of the finger, it can begin suddenly without being preceded by a primary clinically evident infection, it can be exceptionally associated with a post-primary HS of the cheek as in the present case probably due to autoinoculation.